2018
DOI: 10.18393/ejss.376267
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and classification of soils of Yikalo Subwatershed in Lay Gayint District, Northwestern Highlands of Ethiopia

Abstract: Soil resource information is vital for sound land use planning and sustainable fertility management. This study was carried out with the objective of characterizing and classifying soils of Yikalo Subwatershed at Lay Gayint district, Northwestern Ethiopia. Representative soil pedons were opened along topographic positions and described on genetic horizon basis in the field for their morphological characteristics and analyzed in the laboratory for selected physical and chemical soil properties. The soils were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
12
18
0
Order By: Relevance
“…According to AP rating suggested by Cottenie [ 43 ], all land use types are found to contain very low to low (<5 and 5–9 mg/kg, respectively) AP values except forest lands, which contain medium (10–17 mg/kg) AP values. The low soil AP contents observed in the watershed are in agreement with the results reported by Fekadu and colleagues [ 44 ], who reported that the availability of P in most Ethiopian soils has been declining due to fixation, crop removal, and erosion. Weathered soil minerals, organic fertilizer, and inorganic fertilizer are important pools of soil P [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…According to AP rating suggested by Cottenie [ 43 ], all land use types are found to contain very low to low (<5 and 5–9 mg/kg, respectively) AP values except forest lands, which contain medium (10–17 mg/kg) AP values. The low soil AP contents observed in the watershed are in agreement with the results reported by Fekadu and colleagues [ 44 ], who reported that the availability of P in most Ethiopian soils has been declining due to fixation, crop removal, and erosion. Weathered soil minerals, organic fertilizer, and inorganic fertilizer are important pools of soil P [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…The grade of surface horizons were weak and their shape was changed from granular to sub angular blocky, which implies that an existence of surface organic matter. This Finding is in agreement with Fekadu et al (2018) who reported that the presence of OM in the surface soil might be attributed to the formation of granular type of soil. The consistence of soils was slightly hard to hard at dry and slightly friable in the surface horizons of all the pedons when it was in moist, whereas wet consistency varied from sticky and plastic in the meddle slope to very sticky and very plastic in the toe slope position.…”
Section: Soil Structure and Consistencesupporting
confidence: 93%
“…According to Tekalign (1991), the total N contents of the surface layers of pedons 1, 2, and 3 were rated as medium (0.12 to 0.25%) while it was rates as high (> 0.25%) in the surface soil layer of pedon 4. This result is in agreement with the findings of Zeleke and Kibebew (2009), Assen and Yilma (2010);and Fekadu et al (2018) who reported that the direct relation of total N and soil OM as well as high surface OM compared to subsurface soil layer which related with surface biomass. The carbon to nitrogen (C:N) ratio of soils ranged from narrow to the medium range (8:1 to 12:1) which could not adversely affect the mineralization processes (Havlin et al, 1999).…”
Section: Total Nitrogen and Carbon To Nitrogen Ratio (C:n)supporting
confidence: 93%
See 1 more Smart Citation
“…In the study area, surface soil colour patterns showed great variability. This may be related to position in the landscape, slope gradient and organic matter contents (Abate et al, 2014;Hailu et al, 2015, Fekadu et al, 2018. The soil colour patterns of the described profiles (profiles 1, 2, 3, 4 and 5) have become uniformly redder with depth.…”
Section: Site and Morphological Characteristicsmentioning
confidence: 92%